Exercise as an Effective Transgenerational Strategy to Overcome Metabolic Syndrome in the Future Generation: Are We There? - Tibana, Ramires Alsamir; Franco, Octávio Luiz; Pereira, Rinaldo Wellerson; Navalta, James; Prestes, Jonato (Experimental and Clinical Endocrinology & Diabetes, 2017)
Metabolic syndrome (MetS) consist in a combination of cardiovascular risk factors including elevated blood pressure, dyslipidemia, insulin resistance, hyperglycemia and abdominal obesity. Exercise performed before, during and after pregnancy can exert positive effects to counteract MetS risk factors. Here this review aims to analyze the effects of exercise performed before (fathers and mothers) and after periconception (mothers) by using experimental models and its effects on MetS risk factors in offspring. All selected studies investigated the effects of aerobic exercise before, during and after periconception on MetS risk factors in offspring, while no studies utilizing resistance exercise were found. Exercise performed before, and after periconception exerted preventive effects in the offspring, with regards to MetS risk factors. However, more studies focusing on the dose-response of exercise before, and after periconception may reveal interesting results on MetS risk factor in offspring. Thus, the prevention from chronic degenerative diseases can be improved by mother exercise and might be associated with epigenetic mechanisms, such as DNA methylation, hPTMs (histone post translational modifications), non-coding RNAs (ex: MicroRNAs) which results phenotypic modifications by individual genome reprograming. Otherwise, results from paternal exercise are inconclusive at this time.
Keywords: cardiovascular risk factors; exercise transgenerational effects; physical training; epigenetics